From Pastoral to Wilderness: An Eco Marxist Overview Over Late Capitalism Ambivalence in Into The Wild 2007 - Novi Dwi Gitawati; Fitra Mandela; Arie Sugiyartati (Jurnal Sosial Humaniora dan Pendidikan, 2025)
Social science studies can contribute to environmental issues, including through literature, which serves not only as an aesthetic medium but also as a critical reflection to raise ecological awareness. This paper demonstrates that works of fiction can serve as an alternative medium for raising public awareness that environmental degradation is a reality with far-reaching consequences for the sustainability of life. One example is the film Into the Wild (2007), which depicts Christopher McCandless' journey away from the hustle and bustle of the city to ecological regions such as rural areas, mountains, rivers, and ultimately the wilds of Alaska. By employing the concepts of pastoralism and wilderness through an eco-Marxist approach, Christopher's journey can be understood as an ideological discourse that promotes pastoral values while criticizing overly exploitative characteristic of late capitalism towards nature. However, this criticism is ambivalent because the main character remains dependent on the material products of late capitalism to survive. Thus, Into the Wild can be read as both a representation and a problematic critique of late capitalism and the relationship between humans and the environment.